Homens que fazem sexo com homens e participação em ONG's em Belo Horizonte entre 2007 - 2009 - Anibal Fabiao Murure (2011)
The profile of the HIV epidemic indicates that currently the predominant infection among men who have sex with men (MSM), in other words, HIV is more prevalent in men with sexual practices not accepted in society. Actions against the epidemic, discrimination, violence and other diseases that affect MSM are beyond individual initiatives and require a struggle formed by the union. The main objective of this study was to describe and analyze the participation of men who have sex with men in NGOs in Belo Horizonte from 2007 to 2009. It is a cross-sectional study with 265 men who have sex with men in Belo Horizonte. It was used the sampling technique RDS (Respondent Driven Sampling) to recruit elements of the social network of MSM. This RDS technique is a type of sampling chain and it is used to contact populations difficult to reach, where recruitment is made by indication of participants themselves. Recruitment began with participants (seeds) from an NGO in Belo Horizonte, they received incentive coupons and were instructed to recruit other eligible members. For each new volunteer, the participant was reimbursed an amount in Reais. They had a baseline interview to collect socio-demographic, epidemiological and behavioral. Among 265 participants, a minority (17.7%) of men who have sex with men participated in NGOs in Belo Horizonte. About 72.8% have high education, a higher proportion (56.7%) individuals reported being non-white. More than 41.5% of participants were aged less than or equal to 24 years, 205 individuals (77.4%) said they have an income greater than R$ 500.00. In accordance with sexual identity was found that a large majority (90.2%) individuals of identified themselves as MSM and only 9.8% as bisexual or heterosexual. In terms of marital status, 87.1% reported that they are single, most (61.5%) have sufficient knowledge about the transmission of STD / HIV. It was found that a majority (62.3%) have consumed alcohol more than twice a week. There are high proportions on the irregular use of condoms in anal receptive intercourse (41.1%) and insertive (44.5%). The proportions of those who felt discriminated due to sexual orientation in any place (41.5%) were high and those who had a history of having suffered sexual assault, verbal or physical due to sexual orientation (67.2%). The percentage of participation (17.7%) of men who have sex with men participating in NGOs in Belo Horizonte were low. With this low participation can be said that is likely that not all MSM know about the importance and benefits of participation in NGOs. The following variables were associated with greater participation in NGO: non-white skin color, being single, feeling discriminated due to sexual orientation, history of having suffered sexual assault, physical or verbal due to sexual discrimination, receive free condoms in the last 12 months, have made testing anti-syphilis, have a moderate- high chance of becoming infected with HIV, have a history of STD in the last 12 months. The association between having a history of STD in the last 12 months and participation in NGOs may indicate the irregular use of condoms in anal receptive and insertive respectively. It is pertinent to stimulate the participation of MSM in NGOs to promote the regular use of condoms and safe sex practices 14 to reduce the risk of transmission of STD / HIV. It is urgent to expand the distribution of free condoms in all places of public entertainment concentration and MSM. There was no significant difference between sufficiency and insufficiency of knowledge about the transmission of STD / HIV and participation in NGOs. However, it should be improved strategies for HIV prevention for this population group to improve the knowledge and correct the false impression low risk of transmission of STDs and HIV. It is worrying the study show that suffer discrimination based on sexual orientation, have a history of verbal, sexual or physical and history of STD in the last 12 months are associated with participating in NGO. Therefore, NGOs should cooperate with all government bodies, the media and other sectors of civil society to give visibility to the issue of discrimination with a view to advocating for the dissemination of information about the criminalization of all forms of discrimination-based in violence due to sexual orientation and the rights of MSM for when these acts occur, for this population group live without fear.